Best Practices of Leadership Development Method in Kelantan State Secretary (SUK) Office’s Succession Plan - Mohd Ridzuan Sulaiman (2021)
The context of this study only focuses in Kelantan State Secretary (SUK) offices. The theme of the study is about the human resources management practices on leadership or talent development method in order to produce the potential successor in organizations. What is the best leadership development practice of method in Kelantan State Secretary (SUK)? Or is there any other method(s) that can be combined with the existing methods? What is the strategic approach or action can be implement to ensure the sustainability of competent leader for succession plan in its organisational leadership? What is the best assessment method to be used in performances evaluation process of leader? This is a qualitative study. The researcher and used an interview approach to gain opinion and feedback as the primary data for this study. A total of ten (10) respondents were selected from top, middle, and low management, with different designation, post, age, and service period and two (2) of respondents was from an academician or subject matter expert. The researchers choose to conduct semi-structured interviews, in order for to researcher to ask more questions if any, other than the pre-prepared questions. A set of question used as a guideline to ensure the answer given according to the research question and meet the objectives of the study. There are six (7) best practices in leadership development discussed in this study namely coaching, mentoring, networking, job assignment, action learning, subject matter expert and assessment of 360- degree feedback. The findings from this study are interesting. It was found that the Kelantan State Secretary (SUK) office actually practice all the methods but not systematically and structurally. The researcher also indicates that 360-degree feedback methods do not yet implement in the Kelantan State Secretary (SUK) office. The researchers are more likely to get feedback on the application of 360-degree feedback methods. Findings show that young officers are more open to this method. Since this study has constraints in terms of time, data, and information acquired was limited. It affects the findings indirectly and makes this report may not be so comprehensive. However, researchers believe that this study will be seen as a starting point for a more comprehensive follow-up study on the same topic in the future.